PENINGKATAN PEMAHAMAN TENTANG AKTIVITAS MANUSIA DALAM MEMENUHI KEBUTUHAN PEMBELAJARAN IPS MELALUI METODE GROUP TO GROUP EXCHANGE DI KELAS VII.3 SMP NEGERI 34 PALEMBANG (JS (JURNAL SEKOLAH), 2021)
Abstract: Increased Understanding Of Human Activities In Meeting Social Studies Learning Needs Through The Group To Group Exchange Method In Class Vii.3 Of Smp Negeri 34 Palembang. The main material regarding human activities in fulfilling needs is even semester VII grade material in the 2013 curriculum in 2019. The importance of studying this material includes students being able to explain scarcity as a human economic problem, mention the types of human needs, explain the relationship between actions, motives and principles economy, explaining production activities, explaining distribution activities, explaining consumption activities, explaining the link between demand, supply and prices, explaining the role of the market for people's lives, explaining the role of science and technology in economic activities, explaining the role of entrepreneurship in building the Indonesian economy. This research was conducted from February to April 2019 even semester 2018/2019. The research subjects were students of class VII.3 SMP Negeri 34 Palembang with a total of 32 students, on the subject of human activities in meeting needs. And the teacher is accompanied by a collaborator or colleague named Dra. Nurhayati as a teacher observer in classroom action research. Student activeness and learning outcomes of human activities in meeting needs by using the Group to Group Exchange method have increased from cycle I to cycle II. From the results of the learning activities that have been carried out for two cycles, and based on all the discussions and analyzes that have been carried out on Class VII.3 students of SMP Negeri 34 Palembang, it can be concluded that the active learning method Group to Group Exchange has a positive impact in improving student learning outcomes. marked by an increase in student learning completeness in cycle I as many as 16 people or 50.00% complete and 16 more 50.00% students have not completed, while in cycle II an increase of 29 children or by 90.63% and 3 more or 9.38% have not finished studying. Keywords: IPS, Human Activities in Meeting Needs, Group To Group Exchange Abstrak: Peningkatan Pemahaman Tentang Aktivitas Manusia Dalam Memenuhi Kebutuhan Pembelajaran Ips Melalui Metode Group To Group Exchange  Di Kelas Vii.3 Smp Negeri 34 Palembang. Materi pokok tentang aktivitas manusia dalam memenuhi kebutuhan merupakan materi semester genap kelas VII dalam kurikulum 2013 di tahun 2019.  Pentingnya mempelajari matei ini diantaranya siswa dapat menjelaskan kelangkaan sebagai permsalahan ekonomi manusia, menyebutkan jenis-jenis kebutuhan manusia,menjelaskan hubungan antara tindakan, motif dan prinsip ekonomi, menjelaskan kegiatan produksi, menjelaskan kegiatan distribusi, menjelaskan kegiatan konsumsi, menjelaskan kaitan antara permintaan, penawaran dan harga, menjelaskan peran pasar bagi kehidupan masyarakat, menjelaskan peran iptek dalam kegiatan ekonomi, menjelaskan peran kewirausahaan dalam membangun ekonomi indonesia. Penelitian ini dilaksanakan pada bulan  Februari s/d April 2019  semester genap 2018/2019. Subyek penelitian adalah siswa-siswi kelas VII.3 SMP Negeri 34 Palembang dengan jumlah 32 siswa, pada pokok bahasan aktivitas manusia dalam memenuhi kebutuhan. Dan guru ditemani seorang kolaborator atau teman sejawat bernama Dra. Nurhayati sebagai pengamat guru dalam penelitian tindakan kelas. Keaktifan siswa dan Hasil belajar aktivitas manusia dalam memenuhi kebutuhan dengan menggunakan metode  Group to Group Exchange ini mengalami peningkatan dari siklus I, ke siklus II. Dari hasil kegiatan pembelajaran yang telah dilakukan selama dua siklus, dan berdasarkan seluruh pembahasan serta analisis yang telah dilakukan pada siswa Kelas VII.3 SMP Negeri 34 Palembang dapat disimpulkan bahwa metode belajar aktif Group to Group Exchange memiliki dampak positif dalam meningkatkan hasil belajar belajar siswa yang ditandai dengan peningkatan ketuntasan belajar siswa dalam siklus I sebanyak 16 orang  atau           50,00% tuntas dan 16 orang lagi 50,00% siswa belum tuntas, sedangkan pada siklus II meningkat sebanyak 29 orang anak atau sebesar 90,63 % dan 3 orang lagi atau 9,38% belum tuntas belajar. Kata Kunci: IPS,  Aktivitas Manusia Dalam Memenuhi Kebutuhan, Group To Group Exchange